K739 is preferentially targeted over K725 in the deSUMOylation process of neuronal nitric oxide synthase - Xu, Yuxin; Wan, Wei; Wang, Nan (Frontiers in Chemistry, 2025)
IntroductionNeuronal nitric oxide synthase (nNOS) produces nitric oxide (NO) in neurons, essential for learning and memory, but excessive activity causes oxidative/nitrosative stress, contributing to neuropsychiatric disorders. nNOS activation is regulated by calcium-activated calmodulin (CaM) binding and SUMO1 modification at the CaM-binding domain (CaMBD). Our prior studies showed modified CaMBD peptides can modulate NO production in mouse neurons, but their in vivo efficacy, particularly in the middle cerebral artery occlusion (MCAO) model, remains untested. The overlap between SUMO1 and CaM-binding sites raises questions about their interplay and the role of SENP1-mediated deSUMOylation in attenuating nNOS hyperactivity. This study investigates the interactions between CaMBD peptides, SUMO1 modification at K725 and K739, and SENP1-mediated deSUMOylation to develop therapeutic strategies for regulating nNOS activity and mitigating neurotoxicity.MethodsStructural models of the SENP1-SUMO1-nNOS complex were built using X-ray crystallographic data (PDB: 2IY0, 2LL7) and homology modeling, followed by molecular docking with Z-DOCK and 500-ns molecular dynamics simulations using AMBER 24 with the Amber19SB force field. Binding free energies were calculated via MM-GBSA, and interactions analyzed with CPPTRAJ. In vivo, male C57BL/6 mice (4–6 weeks) underwent MCAO. Peptides (25 μg/mouse) were injected into hippocampal CA1 and cortical M1 regions pre-MCAO. Spatial learning and memory were assessed via the Morris water maze, and infarct volumes quantified by TTC staining 24 h post-MCAO. Data were analyzed using one-way ANOVA.ResultsPeptides N0 and N3 showed no significant toxicity, while N1 and N2 reduced survival, likely due to excessive nNOS activation and inflammation. N0 reduced infarct volume but did not improve behavioral outcomes. Molecular dynamics simulations revealed distinct deSUMOylation mechanisms at K725 and K739, with K739 showing stronger SENP1 binding, supported by RMSD and RMSF analyses. Free energy calculations confirmed SENP1’s binding selectivity at K739.DiscussionN0 mitigated ischemia-induced damage in the MCAO model, unlike N2 and N3, suggesting moderate CaMBD affinity prevents excessive nNOS activation and aberrant SUMOylation at K739, critical for neuroprotection. Stronger SENP1 binding at K739 supports targeted deSUMOylation strategies. Further research is needed to optimize peptide therapies and clarify CaM-SUMOylation interactions for nNOS-related disorders.